Closed ended structured questionnaire in fast track familiarization of nurses to conduct telephone follow-up after open carpal tunnel release - Hannula Leevi JS; Tanskanen Tuukka J; Helander-Kuisma Mervi S; Pääkkönen Markus JI (Turkey, 2022)
Background: Open carpal tunnel release (OCTR) due to chronic carpal tunnel syndrome (CTS) is the most common procedure in hand surgery. CTS is often bilateral. A follow-up is required to detect any complications and confirm successful recovery before contralateral procedure is booked. Objectives: The purpose of this study is to evaluate a closed ended questionnaire to assist nurses when starting routine follow-up telephone interviews after carpal tunnel surgery. Methods: In our hospital routine follow-up phone calls to the patients 3 months after OCTR were allocated to nurse practitioners instead of surgeons. Once the practice was started a structured face validated closed ended questionnaire was used to collect data from a total of 61 consecutive patients. Results: Nurse practitioners performed the follow-up independently in 97 % (59/61) of the cases. Ten per cent (6/61) of the patients were assigned further appointments to a surgeon and one patient was referred to an occupational therapist. 2 patients contacted the hospital after the telephone interview because of minor complaints. Patient charts were reviewed 18 months after the phone calls. No missed complications were detected. Conclusions: We conclude that a structured closed ended questionnaire is useful assist in fast track familiarization of nurse practitioners for the follow-up contact after OCTR.